Оценка качества жизни населения с учётом последствий Covid-19 - Маханець, Любов Леонідівна; Гавриляк, Володимир Васильович; Маханець, Богдан Олександрович (ГрГУ им. Янки Купалы, 2021)
The essence of the concept of «quality of life» is analyzed. A model of the dependence of the human development index on the mortality rate of the working-age population and the rate of GNI is built. This model will make it possible to formulate scenarios for the country’s deve-lopment during a pandemic in the context of maintaining an adequate standard of living of the population.
ASSESSMENT OF THE QUALITY OF LIFE OF THE POPULATION TAKING INTO ACCOUNT THE CONSEQUENCES OF COVID-19
Keywords: quality of life, human development index, pandemic, mortality rate of the working age population, GNI rate.